An experimental validation and optimisation tool path strategy for thin walled structure - Alsultaney, Hazem K.; Mohd Ariffin, Mohd Khairol Anuar; Baharudin, B. T. Hang Tuah; Ali, Aidy; Mustapha, Faizal (Universiti Putra Malaysia Press, 2011)
This work was carried out with the aim to optimise the tool path by simulating the removal of material in a finite element environment which is controlled by a genetic algorithm (GA). To simulate the physical removal of material during machining, a finite element model was designed to represent a thin walled workpiece. The target was to develop models which mimic the actual cutting process using the finite element method (FEM), to validate the developed tool path strategy algorithm with the actual machining process and to programme the developed algorithm into the software. The workpiece was to be modelled using the CAD (ABAQUS CAE) software to create a basic geometry co-ordinate system which could then be used to create the finite element method and necessary requirement by ABAQUS, such as the boundary condition, the material type, and the element type.